Endometrial cyst and its changes during pregnancy – a narrative review of the literature - Młodawski, Jakub; Mlodawska, Marta; Malmur, Mariusz; Płusajska, Justyna; Świercz, Grzegorz; Sikorski, Marek (Medical Studies/Studia Medyczne, 2021)
Endometrioma of the ovary (chocolate cyst) is one of the most common tumours of the appendages diagnosed in pregnant patients. In approximately 12% of pregnancies with diagnosed ovarian endometriomas, the process of decidualization, i.e. tumour secretory transformation, occurs under the influence of high progesterone concentrations. Decidualized endometrioma is a benign lesion, but its ultrasound appearance imitates a malignancy; therefore, knowledge of the process and diagnostic possibilities is extremely important for the clinician, and it may limit the number of surgical interventions in pregnant patients. This review discusses the decidualization of endometriosis as well as the ultrasound and biochemical diagnostics of this entity.